In Vitro Fibrinolytic Activity of Recombinant Tissue-Type Plasminogen Activator in the Plasma of Various Primate Species - Lijnen, H R; Marafino, B J, Jr; Collen, D (Thrombosis and Haemostasis, 1984)
The ratio of fibrinolytic to fibrinogenolytic effect of recombinant human tissue-type plasminogen activator was investigated at several concentrations in an in vitro system consisting of 125I-fibrin labeled autologous plasma clots immersed in the plasma of several different primate species. A concentration-dependent fibrinolysis was obtained in each case; however, the degree of fibrinolysis differed markedly from one primate species to the other. At a concentration of 30 IU/ml (300 ng/ml) of recombinant tissue-type plasminogen activator nearly complete thrombolysis was achieved within 4 hr in human plasma, in the chimpanzee, in the cynomolgus macaque, in the bonnet macaque and in the rhesus macaque. The common baboon, the olive baboon and the squirrel monkey were rather resistant to thrombolysis. In all species the thrombolysis achieved was not associated with fibrinogenolysis nor with significant decreases in plasminogen or α2-antiplasmin.
Keywords: Recombinant tissue-type plasminogen activator; Fibrinolysis; Primates